Applications of wasatiyyah in the contemporary Muslim world - Yousif, Ahmad F. (IIUM Press, 2015)
Islam is a religion of peace and moderation, which encourages Muslims to avoid extravagance and excess. The Qur'an addresses the Muslim community as an ummah that is ‘justly balanced’. Muslims, whether in Malaysia or elsewhere, have been advised to live their entire life balancing spiritual and materialistic affairs. While they must focus on religious duties, they are also warned not to neglect worldly affairs. Even when it comes to performing good deeds, Muslims are encouraged to pursue a path of moderation. Today, the absolute majority of Muslims believe that the Prophet’s authentic words, actions, and practices serve only to further endorse the fact that Islam seeks the middle-path and frowns upon any extremism or fanaticism. On numerous occasions, Muhammad (pbuh) stressed the fact that religion should be a matter of ease and not hardship for the people. The Prophet applied this philosophy to his own lifestyle as well.